2016
DOI: 10.1007/s00132-016-3266-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic slipped capital femoral epiphysis

Abstract: Surgical treatment with a DET screw seems to be a safe procedure for both the affected hip and the hip to be treated prophylactically. This method is an adequate alternative to the widespread technique of pinning with K‑wires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Ongoing growth of the femoral neck forces the epiphyseal part of the screw to glide out of the metaphyseal part, as it follows the moving capital femoral epiphysis. A study has shown a decrease in the slip angle by 11⁰ and the alphaangle by about 30⁰ after stabilization of mild and moderate slips with this screw [10]. Most correction (about 60%) was observed during the first postoperative year, stressing the significance of early diagnosis in order to exploit as much as possible of the remaining growth and remodeling potential of the hip.…”
Section: D the Telescopic Screwmentioning
confidence: 89%
See 4 more Smart Citations
“…Ongoing growth of the femoral neck forces the epiphyseal part of the screw to glide out of the metaphyseal part, as it follows the moving capital femoral epiphysis. A study has shown a decrease in the slip angle by 11⁰ and the alphaangle by about 30⁰ after stabilization of mild and moderate slips with this screw [10]. Most correction (about 60%) was observed during the first postoperative year, stressing the significance of early diagnosis in order to exploit as much as possible of the remaining growth and remodeling potential of the hip.…”
Section: D the Telescopic Screwmentioning
confidence: 89%
“…Studies that favor simultaneous surgery of the asymptomatic contralateral hip support the rationale that preventive physis stabilization has low perioperative morbidity and complications compared with therapeutic SCFE surgery [10]. Other studies report that preventive physis surgery may prevent a silent slip and radiologic evidence of Cam-type FAI [21].…”
Section: Simultaneous Stabilization Of the Asymptomatic Contralateralmentioning
confidence: 97%
See 3 more Smart Citations